CLR - Ken Litkowski (Proceedings of the 4th International Workshop on Semantic Evaluations - SemEval '07, 2007)
Objectives To compare the clinical, biological, and technical outcomes of posterior three-unit implant-supported fixed dental prostheses (iFDPs) fabricated from monolithic zirconia (MonoZR) or porcelain-fused-to-metal (PFM). Materials and methods In this prospective randomized controlled trial, partially edentulous patients requiring a posterior three-unit iFDP supported by two implants were randomly assigned to MonoZR or PFM iFDPs. The primary outcome was ceramic fracture. Secondary outcomes included prosthesis survival, complication-free survival, marginal bone level (MBL) changes, peri-implant clinical parameters, and USPHS ratings. Follow-up examinations were performed at 1 and 3 years. Statistical analyses included Kaplan-Meier estimates, Fisher's exact test, and linear mixed-effects models (α = 0.05). Results Fifty-five patients received iFDPs at baseline (MonoZR: n = 28; PFM: n = 27), and 45 completed the 3-year follow-up. Two prosthesis failures occurred, one in each group, both associated with implant loss, with no difference in survival between groups (p = 1.00). Veneering ceramic chipping occurred only in the PFM group (3/23; 13%) and not in the MonoZR group (0/22) (p = 0.11). Complication-free survival, peri-implant clinical parameters, and MBL changes did not differ significantly between groups (p > 0.05). Plaque index and bleeding on probing increased over time, while probing depth and MBL remained stable. Both groups showed high clinical acceptability according to USPHS criteria. Conclusions Both MonoZR and PFM posterior three-unit iFDPs demonstrated high survival and favorable biological outcomes after 3 years. MonoZR showed no chipping events and may represent a promising alternative to PFM for posterior implant-supported restorations. Trial registration German Clinical Trials Register: DRKS00011039.